2014
DOI: 10.1161/circulationaha.114.011204
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor 15, a Marker of Oxidative Stress and Inflammation, for Risk Assessment in Patients With Atrial Fibrillation

Abstract: Background— Growth differentiation factor 15 (GDF-15), high-sensitivity troponin, and N-terminal pro-brain natriuretic peptide levels are predictive of death and cardiovascular events in healthy elderly subjects, patients with acute coronary syndrome, and patients with heart failure. High-sensitivity troponin I and N-terminal pro-brain natriuretic peptide are also prognostic in patients with atrial fibrillation. We evaluated the prognostic value of GDF-15 alone and in addition to clinical character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
1
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(127 citation statements)
references
References 39 publications
5
107
1
14
Order By: Relevance
“…In patients with atrial fibrillation GDF-15 was also shown to be associated with death independently of NT-proBNP and cardiac troponin (22 ).…”
Section: Discussionmentioning
confidence: 94%
“…In patients with atrial fibrillation GDF-15 was also shown to be associated with death independently of NT-proBNP and cardiac troponin (22 ).…”
Section: Discussionmentioning
confidence: 94%
“…GDF15). [302][303][304] Many of these studies have been performed in selected clinical trial cohorts, and the prognostic role in risk stratification requires prospective testing in unselected large 'real-world' cohorts with a broad range of stroke risk and renal function. As in the case of AF prediction, evidence for the additive value of biomarkers for stroke risk prediction from large prospective nonanticoagulated 'real-world' cohorts is limited.…”
Section: Prothrombotic Indices: Coagulation Plateletsmentioning
confidence: 99%
“…Thus, the article by Wallentin et al 14 in the current issue of Circulation is a timely addition to the literature on GDF-15 in AF and describes its systematic analysis in 14 798 patients enrolled in the ARISTOTLE trial. GDF-15 provided prognostic information for stroke, mortality and major bleeding independent of clinical characteristics and clinical risk scores.…”
Section: Circulationmentioning
confidence: 99%
“…However, the data from Wallentin et al 14 suggest that used in combination with clinical risk assessment, GDF-15 may prove to be yet another useful biomarker to improve risk stratification for bleeding and mortality in patients with AF who are receiving anticoagulation therapy. Thus, GDF-15 joins the club of a plethora of biomarkers in AF, only few of which have managed practical application.…”
Section: What Are the Research Gaps?mentioning
confidence: 99%
See 1 more Smart Citation